The second dividend of studying abroad: The impact of international student mobility on academic performance - Johannes Meya; Katharina Suntheim (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper investigates the effect of studying abroad on students success at university. Using an extensive dataset, propensity score matching is applied to account for possible self-selection into international mobility. Our empirical analysis suggests that a temporary study-related visit abroad significantly improves the final university grade, thus granting a second dividend in addition to personal experience. However, it seems that this effect is mainly driven by selective transferring of grades. Moreover, the study shows that a sojourn reduces the probability of finishing studies within the standard time period, suggesting that this dividend comes at a cost.
Keywords: I21; J61; J11; 330; tertiary education; international student mobility; academic performance; grade point average; propensity score matching